Manipulation of single nanodiamonds to ultrathin fiber-taper nanofibers and control of NV-spin states toward fiber-integrated λ-systems. (7th October 2016) - Fujiwara, Masazumi; Yoshida, Kazuma; Noda, Tetsuya; Takashima, Hideaki; Schell, Andreas W; Mizuochi, Norikazu; Takeuchi, Shigeki
Abstract: We report on the coupling of single nitrogen vacancy (NV) centers to ultrathin fiber-taper nanofibers by the manipulation of single diamond nanocrystals on the nanofibers under real-time observation of nanodiamond fluorescence. Spin-dependent fluorescence of the single NV centers is efficiently detected through the nanofiber. We show control of the spin sub-level structure of the electronic ground state using an external magnetic field and clearly observe a frequency fine tuning of m S = ∣ ± 1 〉 . This observation demonstrates a possibility of realizing fiber-integrated quantum λ -systems, which can be used for various quantum information devices including push–pull quantum memory and quantum gates.